The first 62 AGN observed with SDSS-IV MaNGA – IV. Gas excitation and star formation rate distributions. Issue 4 (17th April 2019) - Nascimento, Janaína C do; Storchi-Bergmann, Thaisa; Mallmann, Nícolas D; Riffel, Rogério; Ilha, Gabriele S; Riffel, Rogemar A; Rembold, Sandro B; Schimoia, Jáderson; da Costa, Luiz Nicolaci; Maia, Marcio A G; Machado, Alice D
Abstract: We present maps of the ionized gas flux distributions, excitation, star formation rate (SFR), surface mass density Σ H +, and obtain total values of SFR and ionized gas masses M for 62 active galactic nuclei (AGN) observed with SDSS-IV MaNGA and compare them with those of a control sample of 112 non-active galaxies. The most luminous AGN – with $L(\rm {[O\, {\small III}]}\lambda 5007) \ge 3.8\times 10^{40}\, \mbox{erg}\, \mbox{s}^{-1}$, and those hosted by earlier type galaxies are dominated by Seyfert excitation within 0.2 effective radius R e from the nucleus, surrounded by LINER excitation or transition regions, while the less luminous and hosted by later-type galaxies show equally frequent LINER and Seyfert excitation within $0.2\, R_\mathrm{ e}$ . The extent R of the region ionized by the AGN follows the relation $R\propto \, L(\rm {[O\, {\small III}]})^{0.5}$ – as in the case of the broad-line region. The SFR distribution over the region ionized by hot stars is similar for AGN and controls, while the integrated SFR – in the range 10 −3 –10 M⊙  yr −1 is also similar for the late-type subsample, but higher in the AGN for 75 per cent of the early-type subsample. We thus conclude that there is no signature of AGN quenching star formation in the body of the galaxy in our sample. We also find that 66 per cent of the AGN have higher ionized gas masses M than the controls – in the range 10 5 –3 × 10 7  M⊙ – while 75 per cent of the AGN have higher Σ H + within $0.2\, R_\mathrm{ e}$ than the control galaxies.